Missing Figures: The Role of Domestic and Family Violence in Youth Suicide - Current State of Knowledge Report ... - Meyer, Silke; Atienzar-Prieto, Maria; Fitz-Gibbon, Kate; Moore, Shorna (Griffith University, 2023)
In Australia the national youth suicide statistics are alarming. Suicide accounts for 38 per cent of the deaths among young people aged 15-24 years old. Between 2018-2020 this made suicide the leading cause of death among young Australians (Australian Institute of Health and Welfare, 2022b). Within this, official statistics indicate that suicide is a serious problem among young Australians widely, with disproportionately high suicide rates among young First Nations people and young people with diverse gender and sexual identities. Evidence is now emerging that these, already alarmingly high rates, have further escalated since the beginning of the COVID-19 pandemic. Understanding the factors that contribute to an increased risk of youth suicide is complex. Current evidence suggests that various factors, and their combination, may contribute to a young person’s death by suicide. This evidence further suggests that contributing factors are often lumped together under the umbrella of adverse childhood ...